2021
DOI: 10.3390/ijms222212554
|View full text |Cite
|
Sign up to set email alerts
|

The Laccase Gene Family Mediate Multi-Perspective Trade-Offs during Tea Plant (Camellia sinensis) Development and Defense Processes

Abstract: Laccase (LAC) plays important roles in different plant development and defense processes. In this study, we identified laccase genes (CsLACs) in Camellia sinensis cv ‘Longjing43′ cultivars, which were classified into six subclades. The expression patterns of CsLACs displayed significant spatiotemporal variations across different tissues and developmental stages. Most members in subclades II, IV and subclade I exhibited contrasting expression patterns during leaf development, consistent with a trade-off model f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 56 publications
(83 reference statements)
0
8
0
Order By: Relevance
“…Laccase (LAC; EC1.10.3.2) belongs to a multi-copper oxidase family of enzymes that play a crucial role in plant development and stress responses (Yu et al ., 2021). Various studies have identified the multi-faceted roles of laccases in plants that include cell wall elongation, secondary cell wall formation, lignification, pigmentation, flavonoid biosynthesis, metal ion stress, and seed setting.…”
Section: Discussionmentioning
confidence: 99%
“…Laccase (LAC; EC1.10.3.2) belongs to a multi-copper oxidase family of enzymes that play a crucial role in plant development and stress responses (Yu et al ., 2021). Various studies have identified the multi-faceted roles of laccases in plants that include cell wall elongation, secondary cell wall formation, lignification, pigmentation, flavonoid biosynthesis, metal ion stress, and seed setting.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our previous study revealed that the LTR motif ( cis -acting element involved in low-temperature responsiveness) was predicted to be located in the promoter regions of eight chilling-responsive CsLACs [ 18 ]. Moreover, low-temperature cis -elements were found in the promoters of 8 LACs from Brassica napus [ 29 ], 11 LACs from eggplant [ 17 ], 21 LACs from switchgrass [ 30 ], 12 LACs from tea plant [ 31 ], 45 LACs from wheat [ 32 ], and 16 LACs from peach [ 33 ]. Therefore, the above results indicate that low-temperature cis -elements are essential for the LACs to respond to cold stress.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the PPO gene family in Camellia sinensis (CsPPOs) has been shown to improve pest disease resistance in tea plants (Gulati et al., 1999; Palanisamy & Mandal, 2014); meanwhile, the laccase gene family in C. sinensis (CsLACs) participates in constitutive lignin biosynthesis throughout tea plant growth and development (Yu et al., 2021). Certain R 2 R 3 ‐MYB transcription factors with high specificity and amplification in tea plants regulate secondary metabolite biosynthesis, such as catechins, and specifically activate the CsPPO 1 gene and enhance PPO activity (Huang et al., 2021; Li et al., 2022).…”
Section: Application and Characteristics Of Ppo During The Preharvest...mentioning
confidence: 99%